Analysis of behavioural factors influencing investment decisions: A literature review - Jakub Svoboda (Trends Economics and Management, 2022)
Purpose of the article: The aim of the article is a critical analysis of the views of various authors who have linked their research activities to the topic of behavioural finance, behavioural biases, and risk perceptions in financial markets.Methodology/methods: Qualitative data were aggregated through the method of a systematic review with limits set. A total of 23 papers and publications were located and reviewed. In the paper, the author used logical methods of secondary research such as analysis and synthesis, i.e.the division of the object of research into individual elements and, conversely, the monitoring of connections between individual components (Hendl, 2005).Scientific aim: The scientific benefit is a detailed comprehensive overview of biases that can affect investors' behaviour and risk perception, and a demonstration of risk understanding approaches. The report can serve as a basis for further research and scientific work. Each topic is given the perspective of different authors, which supports the objectivity of the conclusions.Findings: Based on a literature review by multiple authors, the author defined the main behavioural biases. Some of the authors categorise or classify individual biases according to whether they are based on feelings or facts, or according to whether they are heuristics, i.e. mental abbreviations for solving a problem, or cognitive bias, which may be the result of erroneous heuristics. Furthermore, the author found that investor's demographic characteristics, such as age, marital status or education, have a direct impact on his behaviour. The concept of risk can be understood as a state of ignorance of the decision maker, as a variance of possible outcomes, as a danger of negative deviation or as a danger of wrong decision. The perception of risk can be divided to "Risk capacity" - ability to take a risk, and "Risk appetite" - the amount of risk an investor is willing to take in order to gain a reward.Conclusions: The author conducted research of secondary sources, such as of publications and scientific articles dealing with issues of behavioural finance and risk perception. The connection between major behavioural biases and risk perception, and the connection between socio-demographic characteristics and the level of influence of individual investor behavioural biases have been described. All the factors have been found to affect individual investors' perceptions of information to the extent that some individuals perceive the same information differently when making decisions based solely on financial disclosure and make different decisions based on that.
Keywords: D91; G15; G41; 650; behavioural finance; prejudice; bias; behavioural cognitive bias; emotional bias